A MIM injection molding process for NdFeB magnets

By reasonably adjusting the raw material ratio and process flow in the MIM process, including orientation injection molding, extraction degreasing and thermal degreasing, the problem of high carbon oxygen residue in MIM neodymium iron boron magnets is solved, and the molding and production of high-performance magnets is achieved Improved efficiency.

CN119092286BActive Publication Date: 2025-02-11BAOTOU INST MAGNETIC NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411586334.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-11
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

When preparing neodymium iron boron magnets in the existing MIM process, the carbon oxygen residue is high, resulting in low magnet performance, low yield and production efficiency, which cannot meet product requirements.

Method used

By reasonably adjusting the raw material ratio of neodymium iron boron magnets, oriented injection molding, extraction degreasing, thermal degreasing and other processes are adopted to reduce the carbon content and improve magnetic performance.

Benefits of technology

High-performance molding of MIM neodymium iron boron magnets is achieved, with residual magnetization strength ≥1.04 T and maximum magnetic energy product ≥29.7 MGOe, and the yield rate and production efficiency are greatly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119092286B_ABST
    Figure CN119092286B_ABST
Patent Text Reader

Abstract

The invention discloses a MIM injection molding process for a NdFeB magnet, comprising the steps of adjusting raw material ratio, melting and strip-spinning to form strip-shaped sheets, crushing, mixing with a mixed solution of a coupling agent and ethanol, mixing and kneading with a binder, oriented injection molding, extraction degreasing, thermal degreasing, sintering, magnetizing and the like. By optimizing raw material components, oriented injection molding, extraction degreasing, thermal degreasing and the like, near-net-shape forming of a complex shape is achieved, and the MIM NdFeB magnet can achieve excellent magnetic properties with residual magnetization intensity ≥1.04 T and maximum magnetic energy product ≥29.7 MGOe, and greatly improves the magnet yield and production efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of processing NdFeB magnets, and in particular relates to a MIM injection molding process for NdFeB magnets. Background Art

[0002] Permanent magnets play a vital role in promoting the transition from fossil fuels to renewable energy. Their economic and technical significance is increasingly prominent in the field of cutting-edge technology, and they are also widely used in the miniaturization of electronic devices. At present, NdFeB permanent magnets have become an important component of many high-tech products, including electric vehicles, wind turbines, consumer 3C, robots and other high-tech fields.

[0003] NdFeB magnets are generally prepared in several ways, including bonded NdFeB, sintered NdFeB and hot pressed / hot deformed NdFeB. Among them, bonded NdFeB magnets are made of magnetic powder and polymer components, and can be formed using traditional polymer processing techniques, such as calendering, injection molding, extrusion molding and compression molding. Bonded NdFeB is easier to prepare complex-shaped NdFeB magnets, but due to the difficulty in orientation and the non-magnetic nature of the adhesive, the magnetic properties of bonded NdFeB are much lower than those of sintered NdFeB. Sintered NdFeB magnets are manufactured using traditional powder metallurgy routes, and the specific processes include: smelting, belt throwing, hydrogen breaking, air flow grinding, pressing, orientation, sintering, machining, etc. Most sintered magnets have relatively simple geometric shapes. Due to the high brittleness of NdFeB magnets, it is difficult to shape them into complex, small and precise parts using traditional manufacturing processes, and a large amount of NdFeB magnets will be wasted during machining. In addition, hot pressed / hot deformed NdFeB is prepared by a molding process that combines rapid quenching of nanocrystalline NdFeB magnetic powder with hot extrusion. The mechanical properties of hot pressed / hot deformed NdFeB are not good. Due to patent monopoly, the processing cost is high. Also, due to the limitation of molding technology, most of the hot pressed / hot deformed NdFeB are currently made into rings, and the scope of application is also subject to certain restrictions.

[0004] In order to obtain high-performance and complex-shaped NdFeB parts, a process technology based on metal injection molding (MIM) was proposed. MIM technology is a new type of near-net-shape processing technology for metal parts formed by introducing modern plastic injection molding technology into the field of powder metallurgy. It combines the advantages of powder metallurgy and plastic injection molding, can break through the limitations of traditional metal powder compression molding process on product shape, and realize large-scale and efficient forming of metal parts with complex shapes. However, in the current process of using MIM technology to prepare NdFeB magnets, due to the imperfection of the process, the carbon and oxygen residues are high, making the performance of the finished magnets far lower than expected, and the yield and production efficiency of the magnets are also low, which cannot meet the product needs. For example, patent CN 117198672 B discloses a manufacturing process method for injection-molded NdFeB magnets, but does not carefully control the carbon and oxygen content of the magnets. Therefore, the preparation process of low-carbon and high-performance MIM NdFeB needs to be solved urgently. Summary of the invention

[0005] The purpose of the present invention is to provide a MIM injection molding process for NdFeB magnets, reduce the carbon content in the MIM NdFeB magnets, and solve the problems of low magnet performance, low yield and low production efficiency of the current MIM NdFeB magnets.

[0006] To achieve the above object, the present invention provides a MIM injection molding process for NdFeB magnets, comprising the following steps:

[0007] S1. Reasonably adjust the raw material ratio of NdFeB magnets, and mix the raw materials of NdFeB according to the following percentage content:

[0008] Re: 35-40%, Co: 0.2-1.5%, Cu: 0.05-0.6%, Al: 0-0.6%, Ca: 0.05-0.8%, B: 0.9-1.0%, the rest is Fe;

[0009] S2, loading the proportioned raw materials into a vacuum melting belt-spinning furnace, melting and belt-spinning to form belt-shaped flakes;

[0010] S3, loading the prepared strip-shaped flakes into a crusher, and crushing them to form a first NdFeB powder;

[0011] S4, putting the first NdFeB powder, the coupling agent and the mixed solution of ethanol into a mixer, filling the mixer with argon gas as a protective atmosphere, mixing and stirring, and drying after mixing to form a second NdFeB powder;

[0012] S5. Select an adhesive system composed of a graphite-based adhesive, high molecular weight polyethylene and a lubricant, add the adhesive and the second NdFeB powder to a mixer granulator, mix and granulate under a protective atmosphere to form a magnetic mixed granule; wherein the melting temperature of the adhesive is 100°C, the coupling agent does not react with the magnetic powder and the adhesive, and the decomposition temperature of the coupling agent is higher than the temperature during mixing and subsequent injection, and lower than the temperature during subsequent thermal degreasing.

[0013] S6. Injecting the magnetic mixed granules into an injection molding mold through an injection molding device to form an anisotropic first rough blank by molding orientation. The size of the injection molding mold is calculated by combining the thermal shrinkage ratio obtained by multiple experiments on the thermal shrinkage changes of the NdFeB magnets in different directions during the sintering stage with the size of the final product. The general range of the thermal shrinkage ratio obtained by multiple experiments includes: the thermal shrinkage ratio in the easy axis direction is -0.2~-0.1, and the thermal shrinkage ratio in the non-easy axis direction is -0.1~-0.05;

[0014] S7, placing the rough embryo piece into an extraction and degreasing solvent for extraction and degreasing, removing the paraffin wax, and forming a second rough embryo piece;

[0015] S8, placing the second rough blank into a vacuum atmosphere furnace, and performing thermal degreasing at a temperature of 300-850° C. under a protective atmosphere, so that the adhesive in the second rough blank is removed to form a rough blank;

[0016] S9, extract the protective atmosphere in the vacuum furnace using vacuum equipment to keep the vacuum furnace at 1×10 -2 The vacuum degree is below pa, and the temperature is continued to rise to 900-1200℃ for sintering, and the temperature is kept for 5 hours to form a magnet part;

[0017] S10, magnetizing the magnetic part into a neodymium iron boron magnet through a magnetizing device.

[0018] Further, in step S2, the raw materials with good proportions are loaded into the crucible of the vacuum melting belt furnace, and the interior of the vacuum melting belt furnace is evacuated until the vacuum degree in the furnace reaches 3×10 -2 Pa, and after the vacuum is completed, the raw materials in the furnace are preheated. When the metal iron in the crucible begins to turn red, the heating is stopped, and the vacuum operation is performed again to make the vacuum degree in the furnace reach 3×10 -2 Pa, and then high-purity argon is filled into the vacuum melting belt furnace to electromagnetically heat the raw materials in the crucible until the raw materials are completely melted into liquid metal, and then the liquid metal is electromagnetically stirred to form an alloy solution, which is slowly poured onto a water-cooled copper roller with a rotation speed of 0.5-4 m / s, so that the alloy solution forms a strip-like sheet with a thickness of 0.2-0.7mm.

[0019] Further, in step S3, the crusher includes a hydrogen crushing furnace and a jet mill. The strip-shaped flakes are first loaded into the hydrogen crushing furnace, the hydrogen crushing furnace is evacuated, and hydrogen is introduced into the furnace after heating to 200-500°C. In the hydrogen atmosphere, the strip-shaped flakes undergo intergranular and transgranular fractures to form a particle size of 10 -0.5 NdFeB coarse powder of less than 10 mm is then put into a jet mill. Inside the jet mill, a high-speed inert gas flow is accelerated to supersonic speed to cause collision and friction between the NdFeB coarse powders. Finally, the powder is screened out through a sorting wheel with a particle size of 10 -2 The first NdFeB powder with a diameter of 1.17mm.

[0020] Further, in step S6, the NdFeB pellets are heated into a fluid state by a heating unit, and the fluid NdFeB pellets are injected into an injection molding mold through a screw feeding shaft, and a Halbach magnetic array or electromagnet is used in the injection molding mold to provide an orientation magnetic field to orient the first rough blank for molding.

[0021] Furthermore, in step S7, the rough blank is placed in an alkane-based extraction and degreasing solvent, and then subjected to extraction and degreasing at a low temperature of 0-20°C.

[0022] Further, in step S8, the heating rate of the vacuum atmosphere furnace in the thermal debinding stage is in the range of 2-10°C / min.

[0023] Further, in step S9, after the sintering is completed, the blank is placed in a vacuum atmosphere furnace at 1×10 -2 It is naturally cooled to below 50°C under a vacuum degree below pa to form a magnetic part.

[0024] Furthermore, in step S10, before magnetization, the magnetic parts are placed in a polishing machine for polishing, and then the position and shape of the magnetic parts are captured using a machine vision method, and the captured information is transmitted to a computer. After computer analysis and calculation, the grasping information is transmitted to a robot arm, which drives the robot arm to arrange the magnets.

[0025] After adopting the above scheme, the beneficial effects of the present invention are:

[0026] The present invention achieves near-net-shape forming of complex shapes through optimization of raw material composition, oriented injection molding, extraction degreasing, thermal degreasing and other processes. At the same time, the MIM NdFeB magnet can achieve excellent magnetic properties with residual magnetization intensity ≥1.04 T and maximum magnetic energy product ≥29.7MGOe, and greatly improves the magnet yield and production efficiency. The specific effects are as follows:

[0027] 1. The present invention reasonably proportions the raw material components of the NdFeB magnet and adjusts the total amount of rare earth, that is, controls the percentage range of Re to be 35-40%, thereby increasing the volume fraction of the main phase, ensuring sufficient liquid phase to promote sintering density, and adding elements such as copper, gallium, aluminum, and cobalt to the formula. By adjusting the content of these elements, the activity of the rare earth-rich phase is reduced, while the fluidity of the liquid phase is improved, and the uniform wrapping of the rare earth-rich phase with the main phase is achieved, thereby enhancing the demagnetization coupling effect and improving the coercive force of the magnetic steel;

[0028] 2. Through the reasonable selection of adhesive system and the optimization of the two-step degreasing process of extraction degreasing and thermal degreasing, the carbon content in MIM NdFeB magnets is greatly reduced, and the magnetic properties, yield rate and production efficiency are improved;

[0029] 3. By adding coupling agent to the first NdFeB magnetic powder and using protective atmosphere throughout the entire process, especially in the degreasing and sintering stages, the oxygen content is reduced;

[0030] 4. The MIM NdFeB magnets are oriented to make them anisotropic magnets, which greatly improves the magnetic properties;

[0031] 5. The thermal shrinkage ratio is obtained by multiple experiments on the thermal shrinkage changes of MIM NdFeB magnets in different directions during the sintering stage. Combined with the shape and size of the final product, the injection molding mold is reasonably designed, and a vacuum atmosphere furnace is used so that the thermal debinding and sintering stages can be carried out in the same equipment in sequence, ensuring the near-net shape of the final MIM NdFeB magnet;

[0032] 6. The use of automated equipment during the magnetization stage reduces labor costs and speeds up production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a schematic structural diagram of the MIM NdFeB product of the present invention;

[0034] Figure 2 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0035] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0036] The present invention provides a MIM injection molding process for NdFeB magnets. The prepared MIM NdFeB products can be Figure 1 The block-shaped magnet shown has a rectangular groove in the middle. Of course, the shape of the prepared MIM NdFeB product is not limited to this, and can also be a ring or other shape. Figure 2 As shown, the specific MIM injection molding process includes the following steps:

[0037] S1. To regulate the composition of magnetic powder, it is necessary to reasonably adjust the raw material ratio of NdFeB magnets and proportion the raw material components of NdFeB according to the following percentage content:

[0038] Re: 35-40%, Co: 0.2-1.5%, Cu: 0.05-0.6%, Al: 0-0.6%, Ca: 0.05-0.8%, B: 0.9-1.0%, and the rest is Fe; Re is a rare earth metal (rare earth metals), also known as rare earth elements and rare metals. It is a general term for 17 elements in the scandium, yttrium, and lanthanide series in group IIIB of the periodic table. Among them, neodymium (Nd) is the main rare earth element.

[0039] The total amount of rare earth in the formula has a great influence on the performance of the magnetic steel. If the total amount of rare earth is too high, the volume fraction of the main phase will be too low, affecting the remanence of the magnetic steel; if the total amount of rare earth is too low, after reacting with the adhesive, it is impossible to ensure sufficient liquid phase to promote sintering and compaction. Therefore, in the raw material formula of NdFeB, it is necessary to reasonably adjust the total amount of rare earth. The present invention controls Re to 35-40%, reasonably adjusts the total amount of rare earth, increases the volume fraction of the main phase, and ensures sufficient liquid phase to promote sintering and compaction; and adds copper, gallium, aluminum, cobalt and other elements to the formula. Copper, gallium and aluminum have low melting points, which can reduce the activity of the rare earth-rich phase, while improving the fluidity of the liquid phase, achieving uniform wrapping of the main phase, and enhancing the demagnetization coupling effect; cobalt has a high melting point, which prevents the excessive growth of the main phase grains, optimizes the grain boundary structure, and improves the coercive force of the magnetic steel.

[0040] S2. Put the raw materials with good proportion into a vacuum melting belt-spinning furnace, and perform melting and belt-spinning treatment to form belt-shaped flakes.

[0041] Specifically, the raw materials with good proportions need to be loaded into the crucible of the vacuum melting belt furnace, and preferably the raw materials are put in order from high to low melting points, and then the vacuum melting belt furnace is evacuated until the vacuum degree in the furnace reaches 3×10 -2 Pa; after completing the vacuuming, preheat the raw materials in the furnace. When the metal iron in the crucible begins to turn red, stop heating and then perform the vacuuming operation again to make the vacuum degree in the furnace reach 3×10 -2 Pa, and then high-purity argon is filled into the vacuum melting belt furnace to electromagnetically heat the raw materials in the crucible until the raw materials are completely melted into liquid metal, and then the liquid metal is electromagnetically stirred to form an alloy solution, which is slowly poured onto a water-cooled copper roller with a rotation speed of 0.5-4 m / s, so that the alloy solution forms a strip-like sheet with a thickness of 0.2-0.7mm.

[0042] S3, loading the prepared strip-shaped flakes into a crusher, and crushing them to form the first NdFeB powder.

[0043] Specifically, the crusher includes a hydrogen crushing furnace and a jet mill, and needs to be crushed twice. First, the strip-shaped flakes are loaded into the hydrogen crushing furnace, the hydrogen crushing furnace is evacuated, and hydrogen is introduced into the furnace after heating to 200-500°C. In the hydrogen atmosphere, the strip-shaped flakes will undergo intergranular fracture and transgranular fracture to form a particle size of 10 -0.5 NdFeB coarse powder of less than 10 mm is then put into a jet mill. Inside the jet mill, a high-speed inert gas flow is accelerated to supersonic speed to cause collision and friction between the NdFeB coarse powders. Finally, the powder is screened out through a sorting wheel with a particle size of 10 -2 The first NdFeB powder with a diameter of 1.17mm.

[0044] S4. Put the first NdFeB powder, the mixture of coupling agent and ethanol into a mixer, fill the mixer with argon as a protective atmosphere, mix and stir, and dry after mixing to form a second NdFeB powder; wherein the mixer is a three-dimensional mixer, and argon is required as a protective atmosphere at the powder inlet and the coarse powder inlet of the mixer.

[0045] S5, select a bonding agent system composed of a graphite-based bonding agent, a high molecular weight polyethylene and a lubricant, add the bonding agent and the second NdFeB powder to a banburying granulator, and mix and granulate under a protective atmosphere to form a magnetic mixed granule. The protective atmosphere uses argon, so before the bonding agent and the second NdFeB powder are loaded into the banburying granulator, the banburying granulator must be vacuumed using a vacuum device, and high-purity argon is introduced into the banburying granulator after the vacuum treatment, and then the bonding agent and the second NdFeB powder are loaded into the banburying granulator, so that the bonding agent and the second NdFeB powder can be mixed and granulated under a protective atmosphere.

[0046] Preferably, the internal mixer granulator adopts a double rotor design, and the two rotors are engaged with each other in the internal mixer chamber, and strong shearing, extrusion and friction are generated through high-speed rotation, so that the materials are fully mixed and plasticized in the internal mixer chamber. The internal mixer granulator is also provided with a discharge system, and the discharge system is usually designed with a gate valve or a screw discharge device to ensure the smooth discharge and granulation of the materials. In addition, the internal mixer granulator can be controlled by a touch screen operation interface and PLC intelligent control, which is convenient for the operator to monitor the operating status of the equipment, adjust the process parameters and ensure the safe operation of the equipment.

[0047] S6. Injecting the magnetic mixed granules into an injection molding mold via an injection molding device to perform molding orientation to form an anisotropic first rough blank.

[0048] Specifically, a heating unit is used to heat the NdFeB pellets into a fluid state, and the fluid NdFeB pellets are injected into an injection molding mold through a screw feeding shaft. In the injection molding mold, a Halbach magnetic array or an electromagnet is used to provide an orientation magnetic field to orient the first rough blank, so that the final MIM NdFeB magnet is an anisotropic magnet, which greatly improves the magnetic properties.

[0049] The size of the injection molding mold is obtained by performing multiple experiments on the thermal shrinkage changes of the NdFeB magnets in different directions during the sintering stage, and the thermal shrinkage ratio is obtained by combining it with the size of the final product to ensure the near-net forming of the final MIM NdFeB magnet; in addition to the experiment, the thermal shrinkage ratio is cross-validated using simulation, numerical fitting and other methods to obtain a general range of the thermal shrinkage ratio, including: the thermal shrinkage ratio in the easy axis direction is -0.2~-0.1, and the thermal shrinkage ratio in the non-easy axis direction is -0.1~-0.05; wherein, the easy axis, also known as the easy magnetizing axis, is the axis along which the ferromagnet is most easily magnetized along a certain axis or direction; the non-easy axis, also known as the hard magnetizing axis, is the axis that is more difficult to magnetize than the easy axis. That is, in the easy axis direction, the size of the NdFeB magnet after sintering will be 0.1 to 0.2 times smaller than the size before sintering, and in the non-easy axis direction, the size of the NdFeB magnet after sintering will be 0.05 to 0.1 times smaller than the size before sintering. For example, if the sizes in the easy axis direction and the non-easy axis direction before sintering are both 1, then the size in the easy axis direction after sintering will be between 0.8 and 0.9, and the size in the non-easy axis direction will be between 0.9 and 0.95, so that the volume of the NdFeB magnet after sintering will be reduced, so it is necessary to set the size of the injection molding mold larger than the size of the final product. The size ratio of the final product to the injection molding mold is obtained according to the thermal shrinkage ratio, that is, the size of the final product in the easy axis direction is 0.8 to 0.9 times the size of the injection molding mold cavity, and the size on the non-easy axis is 0.9 to 0.95 times the size of the injection molding mold cavity. In the subsequent preparation of the same MIM NdFeB magnets, the size of the injection molding mold can be directly calculated through the general range of heat shrinkage ratio, which reduces the experimental time and reduces the experimental cost.

[0050] S7. Place the rough blank into an extraction degreasing solvent for extraction degreasing to remove the paraffin to form a second rough blank; wherein the extraction degreasing solvent can be an alkane solvent, and the extraction degreasing needs to be carried out at a temperature of 0-20°C so that the degreasing rate can be controlled. After the extraction degreasing, place the second rough blank in a glove box protected by an argon atmosphere for subsequent thermal degreasing and sintering steps. Placing the second rough blank in the glove box can protect its surface from the influence of the external environment, thereby improving the quality and reliability of the product.

[0051] S8. Place the second rough blank into a graphite box, then place the graphite box containing the second rough blank into a vacuum atmosphere furnace, use a mixed atmosphere of hydrogen and argon as a protective atmosphere, and heat up to 300-850°C at a heating rate of 2-10°C / min under the protective atmosphere. Perform thermal degreasing at this temperature to remove the adhesive in the second rough blank to form a blank.

[0052] Preferably, the vacuum atmosphere furnace also uses a touch screen operation interface and PLC intelligent control, and also has a temperature measuring device inside, which is convenient for the operator to monitor the operating status of the equipment, the real-time temperature inside the furnace and adjust the heating rate.

[0053] S9, extract the protective atmosphere in the vacuum furnace using vacuum equipment to keep the vacuum furnace at 1×10 -2 The vacuum degree is below pa, and the temperature is continued to rise to 900-1200℃ for sintering, and the temperature is kept for 5 hours. After the sintering is completed, the blank needs to be placed in a vacuum atmosphere furnace at 1×10 -2 The magnet is naturally cooled to below 50°C under a vacuum degree of less than pa to form a magnet. In addition, the use of a vacuum atmosphere furnace allows the hot debinding and sintering stages to be carried out in the same equipment in sequence, ensuring the near-net shape of the final MIM NdFeB magnet.

[0054] S10, magnetizing the magnetic part into a neodymium iron boron magnet through a magnetizing device.

[0055] Preferably, before magnetization, the magnet is placed in a polishing machine for polishing. The polishing machine can be a vibration polishing machine, and the polishing abrasive can be a high-hardness grinding stone (such as brown corundum grinding stone, ceramic grinding stone, high-aluminum porcelain grinding stone or high-frequency porcelain grinding stone). The polishing liquid must contain an antioxidant.

[0056] After polishing and before magnetization, use automated equipment to arrange the magnets. Preferably, use machine vision to capture the position and shape of the magnets, and transmit the captured information to a high-performance computer. After computer analysis and calculation, transmit the grasping information to a robot arm, and drive the robot arm to arrange the magnets.

[0057] In addition, automated equipment and magnetizing equipment can be used on an automated production line. After the automated equipment completes the arrangement of the magnetic parts, multiple magnetic parts are placed in the magnetizing equipment in turn through a conveyor belt for magnetization, thereby realizing automated processing and production, reducing manpower input, and accelerating production efficiency.

[0058] In steps S4-S8, the present invention selects a reasonable adhesive system, with a graphite-based adhesive as the main body, a polymer polyethylene and a lubricant as the adhesive system, the adhesive of this system is short-chain and easy to remove during thermal degreasing, has a certain rigidity and strength after cooling, and the melting temperature of the adhesive is 100°C, the viscosity of the adhesive during injection is relatively small, and its viscosity fluctuation is small. Through the reasonable selection of the adhesive system and the optimization of the two-step degreasing process of extraction degreasing and thermal degreasing, the carbon content in the MIM NdFeB magnet is greatly reduced, and the magnetic properties, yield rate and production efficiency are improved.

[0059] It should be noted that the coupling agent should also be selected reasonably. Silane coupling agent can be used. The coupling agent cannot react with magnetic powder and adhesive. The decomposition temperature of the coupling agent should be higher than the temperature during mixing granulation and injection, and lower than the temperature during thermal degreasing, so that it can be completely removed during the thermal degreasing stage. By adding the coupling agent to the first NdFeB magnetic powder and using a protective atmosphere throughout the entire process, especially in the degreasing and sintering stages, the oxygen content can be reduced, further improving the yield and production efficiency of the magnet.

[0060] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0061] Embodiment 1:

[0062] The raw material components of NdFeB are proportioned according to the following percentages:

[0063] Re: 35%, Co: 0.7%, Cu: 0.25%, Al: 0.1%, Ca: 0.3%, B: 0.9%, and the rest is Fe. Then, the raw material components are subjected to the above step S2-10 to complete the preparation of the MIM NdFeB magnet.

[0064] Embodiment 2:

[0065] The difference between this embodiment and embodiment 1 is that the raw material components of NdFeB are proportioned according to the following percentage contents:

[0066] Re: 37%, Co: 0.7%, Cu: 0.25%, Al: 0.1%, Ca: 0.2%, B: 0.9%, and the rest is Fe.

[0067] Embodiment 3: The difference between this embodiment and embodiment 1 is that the raw material components of NdFeB are proportioned according to the following percentage contents:

[0068] Re: 39%, Co: 0.7%, Cu: 0.25%, Al: 0.1%, Ca: 0.2%, B: 0.9%, and the rest is Fe.

[0069] The final products obtained in the above examples 1-3 were tested for performance, and the results are shown in the following table:

[0070]

[0071] Performance tests were performed on the final products obtained in the above embodiments 1-3. It was found that the MIM NdFeB magnets prepared in the embodiments of the present invention can achieve excellent magnetic properties of residual magnetization intensity ≥1.04 T, maximum magnetic energy product ≥29.7 MGOe, coercive force ≥12.1KOe, and yield rate ≥95%. The above performances are greatly improved compared with the existing preparation process.

[0072] The above description is only a preferred embodiment of the present invention and is not a limitation on the design of this case. Any equivalent changes made based on the design key of this case shall fall within the protection scope of this case.

Claims

1. A MIM injection molding process for NdFeB magnets, characterized in that: The following steps are involved: S1. Reasonably adjust the raw material ratio of NdFeB magnets, and mix the raw materials of NdFeB according to the following percentage content: Re: 35-40%, Co: 0.2-1.5%, Cu: 0.05-0.6%, Al: 0-0.6%, Ca: 0.05-0.8%, B: 0.9-1.0%, the rest is Fe; S2, loading the proportioned raw materials into a vacuum melting belt-spinning furnace, melting and belt-spinning to form belt-shaped flakes; S3, loading the prepared strip-shaped flakes into a crusher, and crushing them to form a first NdFeB powder; S4, putting the first NdFeB powder, the coupling agent and the mixed solution of ethanol into a mixer, filling the mixer with argon gas as a protective atmosphere, mixing and stirring, and drying after mixing to form a second NdFeB powder; S5. Select an adhesive system composed of a graphite-based adhesive, a high molecular weight polyethylene and a lubricant, add the adhesive and the second NdFeB powder to a mixer granulator, mix and granulate under a protective atmosphere to form a magnetic mixed granular material, wherein the melting temperature of the adhesive is 100°C, the coupling agent does not react with the magnetic powder and the adhesive, and the decomposition temperature of the coupling agent is higher than the temperature during mixing and subsequent injection, and lower than the temperature during subsequent thermal degreasing; S6. Injecting the magnetic mixed granules into an injection molding mold through an injection molding device to form an anisotropic first rough blank by molding orientation. The size of the injection molding mold is calculated by combining the thermal shrinkage ratio obtained by multiple experiments on the thermal shrinkage changes of the NdFeB magnets in different directions during the sintering stage with the size of the final product. The general range of the thermal shrinkage ratio obtained by multiple experiments includes: the thermal shrinkage ratio in the easy axis direction is -0.2~-0.1, and the thermal shrinkage ratio in the non-easy axis direction is -0.1~-0.05; S7, placing the rough embryo piece into an extraction and degreasing solvent for extraction and degreasing, removing the paraffin wax, and forming a second rough embryo piece; S8, placing the second rough blank into a vacuum atmosphere furnace, and performing thermal degreasing at a temperature of 300-850° C. under a protective atmosphere, so that the adhesive in the second rough blank is removed to form a rough blank; S9, extract the protective atmosphere in the vacuum furnace using vacuum equipment to keep the vacuum furnace at 1×10 -2 The vacuum degree is below pa, and the temperature is continued to rise to 900-1200℃ for sintering, and the temperature is kept for 5 hours to form a magnet part; S10, magnetizing the magnetic part into a neodymium iron boron magnet through a magnetizing device.

2. The MIM injection molding process of a NdFeB magnet as claimed in claim 1, characterized in that: In step S2, the raw materials with good proportions are loaded into the crucible of the vacuum melting belt furnace, and the interior of the vacuum melting belt furnace is evacuated until the vacuum degree in the furnace reaches 3×10 -2 Pa, and after the vacuum is completed, the raw materials in the furnace are preheated. When the metal iron in the crucible begins to turn red, the heating is stopped, and the vacuum operation is performed again to make the vacuum degree in the furnace reach 3×10 -2 Pa, and then high-purity argon is filled into the vacuum melting belt furnace to electromagnetically heat the raw materials in the crucible until the raw materials are completely melted into liquid metal, and then the liquid metal is electromagnetically stirred to form an alloy solution, which is slowly poured onto a water-cooled copper roller with a rotation speed of 0.5-4 m / s, so that the alloy solution forms a strip-like sheet with a thickness of 0.2-0.7mm.

3. The MIM injection molding process of a NdFeB magnet as claimed in claim 1, characterized in that: In step S3, the crusher includes a hydrogen crushing furnace and a jet mill. The strip-shaped flakes are first loaded into the hydrogen crushing furnace, which is evacuated and heated to 200-500°C. After that, hydrogen is introduced into the furnace. In the hydrogen atmosphere, the strip-shaped flakes undergo intergranular and transgranular fractures to form a particle size of 10 -0.5 NdFeB coarse powder of less than 10 mm is then put into a jet mill. Inside the jet mill, a high-speed inert gas flow is accelerated to supersonic speed to cause collision and friction between the NdFeB coarse powders. Finally, the powder is screened out through a sorting wheel with a particle size of 10 -2 The first NdFeB powder with a diameter of 1.17mm.

4. The MIM injection molding process of a NdFeB magnet as claimed in claim 1, characterized in that: In step S6, the NdFeB pellets are heated into a fluid state by a heating unit, and the fluid NdFeB pellets are injected into an injection molding mold through a screw feed shaft. A Halbach magnetic array or electromagnet is used in the injection molding mold to provide an orientation magnetic field to orient the first rough blank.

5. The MIM injection molding process of a NdFeB magnet as claimed in claim 1, characterized in that: In step S7, the rough blank is placed in an alkane-based extraction and degreasing solvent, and then subjected to extraction and degreasing at a low temperature of 0-20°C.

6. The MIM injection molding process of a NdFeB magnet according to claim 1, characterized in that: In step S8, the heating rate of the vacuum atmosphere furnace during the thermal debinding stage is in the range of 2-10°C / min.

7. The MIM injection molding process of a NdFeB magnet according to claim 1, characterized in that: In step S9, after sintering, the blank is placed in a vacuum furnace at 1×10 -2 It is naturally cooled to below 50°C under a vacuum degree below pa to form a magnetic part.

8. The MIM injection molding process of a NdFeB magnet according to claim 1, characterized in that: In step S10, before magnetization, the magnetic parts are placed in a polishing machine for polishing, and then the position and shape of the magnetic parts are captured using a machine vision method, and the captured information is transmitted to a computer. After computer analysis and calculation, the grasping information is transmitted to a robot arm, which drives the robot arm to arrange the magnets.

Citation Information

Patent Citations

  • A manufacturing process for injection molded NdFeB magnets

    CN117198672B

  • Net shaped aligned and sintered magnets by modified MIM processing

    CN104715918A

  • High-performance composite bonding rare earth permanent magnet material

    CN105161241A